2018
DOI: 10.3171/2016.10.jns161825
|View full text |Cite
|
Sign up to set email alerts
|

Microvascularization of Grade I meningiomas: effect on tumor volume, blood loss, and patient outcome

Abstract: OBJECTIVE Quantitative assessment of tumor microvascularity has the potential to improve prognostication, advance understanding of tumor biology, and help narrow potential molecular therapies. While the role of tumor microvascularity has been widely studied in meningiomas, this study examines both the role of automated measurements and the impact on surgical outcome. METHODS Two hundred seven patients with Grade I meningiomas underwent surgery between 1996 and 2011. Tissue samples from each patient were retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…VEGF level did not differ significantly in patients with small or large amounts of intraoperative bleeding. This might be due the absence of a logical or statistical cutoff point for the amount of bleeding, and our result was consistent with previous studies (Karsy et al, 2017). In addition, Sonoda et al, (2003) observed a correlation between higher serum VEGF with grade tumor.…”
Section: Discussionsupporting
confidence: 93%
“…VEGF level did not differ significantly in patients with small or large amounts of intraoperative bleeding. This might be due the absence of a logical or statistical cutoff point for the amount of bleeding, and our result was consistent with previous studies (Karsy et al, 2017). In addition, Sonoda et al, (2003) observed a correlation between higher serum VEGF with grade tumor.…”
Section: Discussionsupporting
confidence: 93%
“…Vascularization is commonly found in rapidly growing tumors and corresponds to a higher metabolic demand of these lesions. Correspondingly, Karsy et al reported correlations of vascularization and tumor volume in a series of grade I meningiomas [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It appears reasonable that an increased tumor vascularization might correspond to a higher metabolic demand in biological aggressive lesions displaying more rapid tumor growth. An increased vessel density has also been described in a portion of benign meningiomas [ 16 ] and was shown to correlate with an augmented preoperative tumor volume [ 17 ]. Hence, further elucidation of the role of angiogenesis in grade I meningiomas might help to estimate the risk for tumor recurrence and the potential of anti-angiogenic drugs in these tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The recent reappraisal of the clinical significance of the resection rate on long‐term tumor control reflects the recent awareness that the biological characteristics of each tumor should be properly assessed to implement personalized treatment. MIB‐1 LI has been well established for assessing the proliferative ability of meningioma cells and predicting recurrence …”
Section: Discussionmentioning
confidence: 99%